Modifikasi Oven Bekas sebagai Alat Pengering Multi Fungsi - Subandi Subandi (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
Laboratory equipment is a basic nees that must be available in the laboratory to support the implementation of learning for students both the laboratory, research, and experiments on the theory gained in lectures. Some units laboratory equipment such as ovens, incubators and others were damaged and difficult to repair because the parts difficult to obtain or the cost to repair is very high, the procurement of new equipment not necessarily every year could be sufficient so that the equipment that is needed is not available, thus the implementation of laboratory services could not walk properly. Modification of the second-hand oven into the multi function dryer is a refinement of previous studies is an oven that can be used for various drying, thus will greatly assist the smooth implementation of learning and service in the laboratory. It the quality of learning and good laboratory services, is expected to produce graduates who have the competence of industrial and entrepreneurial spirit and morality so as to compete at both local and regional levels in order to face global competition.Â Keywords: equipment, laboratory services, graduates who are competent